Early breastfeeding practices contribute to exclusive breastfeeding in Bangladesh, Vietnam and Ethiopia - Nguyen, Phuong Hong; Kim, Sunny S.; Tran, Lan Mai; Menon, Purnima; Frongillo, Edward A. (John Wiley & Sons, 2020)
Limited evidence exists on the complex relationship among interventions, early initiation of breastfeeding (EIBF), prelacteal feeding and exclusive breastfeeding (EBF). We examined whether early breastfeeding practices are associated with EBF and how much improving EIBF and non‐prelacteal feeding contributes to increased prevalence of EBF. Survey data were collected in 2010 and 2014 as part of impact evaluations of Alive & Thrive (A&T) interventions to improve infant and young child feeding (IYCF) practices in Bangladesh, Vietnam and Ethiopia. Multivariable logistic regression analyses were used to examine effects of interventions and early breastfeeding practices on EBF. Structural equation modelling quantified the direct and indirect effects of interventions (via improving EIBF and non‐prelacteal feeding) on EBF. Although breastfeeding is nearly universal in all three countries (≥98%), delayed initiation of breastfeeding is prevalent (>60%) and prelacteal feeding is common. EIBF alone was not associated with EBF, whereas non‐prelacteal feeding was associated with 1.6–3.5 higher odds of EBF. Intervention exposure affected breastfeeding practices in all three countries; these impacts were amplified among those who practiced EIBF or non‐prelacteal feeding [odds ratio (OR) = 11 and 27.5 in Bangladesh and 6.5 and 11.5 in Vietnam, respectively]. The paths through EIBF and non‐prelacteal feeding explained 13%–18% of the effect of the interventions on EBF. Early breastfeeding practices influence EBF, but interventions aimed only at the initiation and early days of breastfeeding will be inadequate to promote EBF. Social and behaviour change interventions should simultaneously target EIBF, non‐prelacteal feeding and EBF to support optimal breastfeeding practices.